Mechanical, thermal, and morphological properties of (eggshell powder)-filled natural rubber latex foam - Bashir, A.S.M. (John Wiley and Sons Ltd, 2017)
Eggshell (ES) waste is available in a huge quantity and has been listed worldwide as one of the worst environmental problems. This study aimed to use, for the first time, ES powder (ESP) as filler in natural rubber latex foam (NRLF). Tensile strength of NRLF incorporated with ESP initially drops at low ESP filler loading and then increases with the increment of filler loading from 5 to 10 parts by weight per hundred parts of resin (phr). As the ESP filler loading increases up to 10 phr, M100, compression stress, compression set, hardness, rubber filler interaction, and density increase. Meanwhile, elongation at break and recovery percentage of compression set decrease as the filler loading increases up to 10 phr. Field emission scanning electron microscopy results indicate that even at 10 phr of ESP loading, the fillers are homogenously dispersed in the matrix without agglomerations. However, the thermal stability of NRLF decreases with the incorporation of ESP, as indicated by results of thermogravimetric analysis. J. VINYL ADDIT. TECHNOL., 23:3–12, 2017. © 2015 Society of Plastics Engineers. © 2015 Society of Plastics Engineers